TAMI-06. PRECLINICAL MODELS REVEAL BRAIN-MICROENVIRONMENT SPECIFIC METABOLIC DEPENDENCIES IN GLIOBLASTOMA. (9th November 2020) - Minami, Jenna; Bayley, Nicholas; Tse, Christopher; Zhu, Henan; Morrow, Danielle; Yong, William; Liau, Linda; Cloughesy, Timothy; Graeber, Thomas; Nathanson, David
Abstract: Metabolic reprogramming is a hallmark of cancer, and malignant cells must acquire metabolic adaptations to fuel neoplastic progression. Mutations or changes in metabolic gene expression can impose nutrient dependencies in tumors, and even in the absence of metabolic defects, cancer cells can become auxotrophic for particular nutrients or metabolic byproducts generated by other cells in the tumor microenvironment (TME). Conventional cell lines do not recapitulate the metabolic heterogeneity of glioblastoma (GBM), while primary cultured cells do not account for the influences of the microenvironment and the blood brain barrier on tumor biology. Additionally, these systems are under strong selective pressure divergent from that in vivo, leading to reduced heterogeneity between cultured tumor cells. Here, we describe a biobank of direct-from-patient derived orthotopic xenografts (GliomaPDOX) and gliomaspheres that reveal a subset of gliomas that, while able to form in vivo, cannot survive in vitro. RNA sequencing of tumors that can form both in vivo and in vitro (termed "TME-Indifferent") compared to that of tumors that can only form in vivo (termed "TME-Dependent") revealed transcriptional changes associated with altered nutrient availability, emphasizing the unique metabolic programs impacted by the tumor microenvironment. Furthermore, TME-dependent tumors lack metabolic signatures associated with nutrient biosynthesis, thus indicating a potential dependency of these tumors on scavenging specific nutrients from the extracellular milieu. Collectively, these data emphasize the metabolic heterogeneity within GBM, and reveal a subset of gliomas that lack metabolic plasticity, indicating a potential brain-microenvironment specific metabolic dependency that can be targeted for therapy.